Spin wave stiffness and damping in a frustrated chiral helimagnet Co_{8}Zn_{8}Mn_{4} as measured by small-angle neutron scattering - V. Ukleev; K. A. Pschenichnyi; O. Utesov; K. Karube; S. Mühlbauer; R. Cubitt; Y. Tokura; Y. Taguchi; J. S. White; S. V. Grigoriev (Physical Review Research, 2022)
Multiple intriguing low-temperature phenomena have recently been discovered in the family of chiral cubic Co-Zn-Mn compounds with a β-Mn-type structure. In particular, Co_{8}Zn_{8}Mn_{4} displays a reduction of the helical spiral pitch on cooling along with lattice shape transformations of metastable skyrmions and the manifestation of peculiar magnetic textures due to strong magnetocrystalline anisotropy. Here we report on temperature-dependent measurements of helimagnon excitations in the field polarized regime Co_{8}Zn_{8}Mn_{4} using the spin-wave (SW) small-angle neutron-scattering technique. By applying a new analytical expression to interpret the data, quantitative estimates for both SW stiffness and damping are extracted across a wide temperature range between 70 and 250 K. We speculate that their nontrivial temperature dependencies arise due to the effects of magnetic frustration arising from Mn magnetic moments, which is further reflected in continuous variations of both exchange and Dzyaloshinskii-Moriya interactions.